Intersectoral Dynamics and Economic Growth in Ecuador - Fiess, Norbert M.; Verner, Dorte (World Bank, Washington, DC, 2014)
The authors analyze sectoral growth in Ecuador, using multivariate co-integration analysis. They find significant long-run relationships between the agricultural, industrial, and service sectors. Moreover, they are able to derive dynamic sector models that combine the short-run links between the three sectors with long-run dynamics. When disaggregate the three sectors into their intra-sectoral components, they discover many interesting relationships that contribute to a better understanding of inter- and intra-sectoral dynamics in the context of Ecuadorian economic growth. Their findings suggest that more attention should be paid to inter-dependencies in sectoral growth, since an improved understanding of inter-sectoral dynamics may facilitate the implementation of policy aimed at increasing economic growth in Ecuador. There appears to be no direct link between the oil sector, and the non-oil industrial sectors. But strong evidence supports co-integration between the oil industry, and financial services, as well as between the oil industry, and public services. This means, among other things, that the oil industry is likely to affect other sectors through the financial sector, the public sector, or both.